The methylation patterns of the IGF2 and IGF2R genes in bovine spermatozoa are not affected by flow-cytometric sex sorting. - CARVALHO, J. O. (2012)
The objectives of this study were to investigate the effect of sexing by flow cytometry on the methylation patterns of the IGF2 and IGF2R genes. Frozen-thawed, unsorted, and sex-sorted spermsamples fromfour Nellore bulls were used. Each ejaculate was separated into three fractions: non-sexed (NS), sexed forX-sperm(SX), and sexed for Y-sperm (SY). Sperm were isolated from the extender, cryoprotectant, and other cell types by centrifugation on a 40:70%Percoll gradient, and spermpellets were used for genomic DNA isolation. DNA was used for analyses of the methylation patterns by bisul?te sequencing.Methylation status of the IGF2 and IGF2Rgeneswere evaluated by sequencing 195 and 147 individual clones, respectively. No global differences in DNAmethylation were found between NS, SX, and SY groups for the IGF2 (P¼0.09) or IGF2R genes (P¼0.38). Very speci?c methylation patterns were observed in the 25th and 26th CpG sites in the IGF2R gene. representing higher methylation in NS than in the SX and SY groups compared with the other CpG sites. Further, individual variation in methylation patterns was found among bulls. In conclusion, the sex-sorting procedure by flow cytometry did not affect the overall DNA methylation patterns of the IGF2 and IGF2R genes, although individual variation in their methyla-tion patterns among bulls was observed.